Video Game Experience and Gender as Predictors of Performance and Stress During Supervisory Control of Multiple Unmanned Aerial Vehicles. (September 2015) - Lin, Jinchao; Wohleber, Ryan; Matthews, Gerald; Chiu, Peter; Calhoun, Gloria; Ruff, Heath; Funke, Gregory
To keep pace with increasing applications of Unmanned Aerial Vehicles (UAVs), recruitment of operators will need to be expanded to include groups not traditionally engaged in UAV pilot training. The present study may inform this process as it investigated the relationship between video game experience and gender on performance of imaging and weapon release tasks in a simulated multi-UAV supervisory control station. Each of 101 participants completed a 60 minute experimental trial. Workload and Level of Automation (LOA) were manipulated. Video gaming expertise correlated with performance on a demanding surveillance task component. Video gamers also placed more trust in the automation in demanding conditions and exhibited higher subjective task engagement and lower distress and worry. Results may encourage recruitment of UAV operators from nontraditional populations. Gamers may have a particular aptitude, and with gaming experience controlled, women show no disadvantage relative to men.